Ocular dynamics and skeletal systems. - Schovanec, L. (IEEE Control systems magazine)
Issues that are central to the modeling and analysis of a human movement system include musculotendon dynamics, the kinetics and kinematics of the biomechanical system, and the determination of neurological controls that are pertinent to a particular movement. In formulating a model for a biological control system, realism and complexity are always competing concerns. Human motion involves neurons, muscles, chemical reactions, bones, joints, and ligaments. How realistic can a model be made and still be simple enough for practical implementation and analytical tractability? What features of these enormously complex mechanisms are essential to include in the model, and which may be left out? Clearly, part of the answer to these questions lies in the specific model to be analyzed and the purpose for which it is to be used. The article focuses on the dynamics and control of ocular and skeletal systems. The discussion of these systems provides insights into modeling issues that are common to the study of human movement systems